(1023) Economic and Statistical Consideration in the Formulation of Engel and the Effect of Household Size and Composition of Consumption الاعتبارات الاقتصادية والإحصائية في صياغة إنجل وتأثير حجم الأسرة وتركيب الاستهلاك - Azza El-Gibaly (INP., 2020)
The Engel Curve describes the relationship between household income and expenditure on specific goods or services. Analyzing family budget data helps refine this relationship using statistical models derived from household budget surveys. Understanding different forms of the Engel Curve is crucial for evaluating consumption patterns and economic behavior. This paper discusses commonly used Engel Curve models in the literature and examines the economic and statistical factors that influence their selection and application.